THE PROBLEM OF SECONDARY DRY EYE SYNDROME IN THE CONTEXT OF ORGAN-SAVING RADIOTHERAPY FOR CHOROIDAL MELANOMA - Ye. I. Gyuntner; I. Ye. Panova (Опухоли головы и шеи)
After brachytherapy for choroidal melanoma, mild and moderate secondary dry eye syndrome was established in 87.2 and 12.8 % of the patients, respectively. Biomicroscopic changes in the ocular surface were seen in the postradiation period over time. Out of the functional studies, there was timing of precorneal tear film rupture, meniscometry using optical coherent tomography, which proved to be of the most informative value. The findings suggested that at 1 year of brachytherapy for choroidal melanoma, the secondary dry eye syndrome was accompanied by a significant reduction in the rupture time for the precorneal tear film and by a decrease in the height of the lower tear meniscus.